2021
DOI: 10.1038/s41438-021-00492-4
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Fra a 1.02 in strawberry fruits causes transcriptomic and metabolic changes compatible with an altered defense response

Abstract: The strawberry Fra a 1 proteins belong to the class 10 Pathogenesis-Related (PR-10) superfamily. In strawberry, a large number of members have been identified, but only a limited number is expressed in the fruits. In this organ, Fra a 1.01 and Fra a 1.02 are the most abundant Fra proteins in the green and red fruits, respectively, however, their function remains unknown. To know the function of Fra a 1.02 we have generated transgenic lines that silence this gene, and performed metabolomics, RNA-Seq, and hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Similarly, previous studies have further proposed that the loss of GST function can cause a reduction in anthocyanidin accumulation in concert with the loss of color development in other plants, such as MdGST in apple, VviGST4 in grape, LcGST4 in litchi, and RAP in strawberry [60][61][62][63]. More recently it was shown that the stable downregulation of the PR-10 protein Fra a 1 triggered decreased GSH concentration and lower GST expression levels in the transgenic fruits (Figure 4) [64]. As additional endorsement, our results demonstrate the binding of GSH and GSSG to the PR-10 protein Mal d 1, which may be of significance for the regulation of the anthocyanin/flavonoid accumulation in apples.…”
Section: Relationships Of Pr-10 Proteins Glutathione and Glutathione S-transferase Expressionsupporting
confidence: 52%
“…Similarly, previous studies have further proposed that the loss of GST function can cause a reduction in anthocyanidin accumulation in concert with the loss of color development in other plants, such as MdGST in apple, VviGST4 in grape, LcGST4 in litchi, and RAP in strawberry [60][61][62][63]. More recently it was shown that the stable downregulation of the PR-10 protein Fra a 1 triggered decreased GSH concentration and lower GST expression levels in the transgenic fruits (Figure 4) [64]. As additional endorsement, our results demonstrate the binding of GSH and GSSG to the PR-10 protein Mal d 1, which may be of significance for the regulation of the anthocyanin/flavonoid accumulation in apples.…”
Section: Relationships Of Pr-10 Proteins Glutathione and Glutathione S-transferase Expressionsupporting
confidence: 52%
“…Most of them have been reported to positively regulate plant defense responses against pathogens. For instance, PR‐10 superfamily participates in the defense against pathogens in the ripe strawberry fruits (Orozco‐Navarrete et al., 2021). In addition, previous research hypothesized that overexpression of the gene encoding nonsymbiotic hemoglobin can interfere in the dynamics of ROS production and NO scavenging, and then reduce plant susceptibility to Meloidogyne incognita (Basso et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report found that priming strawberry leaves with the phytohormone salicylic acid (SA) leads to upregulation of PR genes, including PR10 genes, and concomitant increases in PA levels (Feng et al., 2020). In another study, silencing Fra a 1.02 led to downregulation of WRKY‐type transcription factors and ABC and MATE transporters and to a diminished content of the hormones jasmonic acid, SA, and indole acetic acid, suggesting a role in stress responses (Orozco‐Navarrete et al., 2021). This report and others indicate that stress‐induced expression of PR10s, including Fra a proteins, can potentially orchestrate a metabolic shift via undiscovered roles as auxiliary proteins, chemical chaperones, or regulatory elements.…”
Section: Pathogenesis‐related Proteins; From Molecular Chaperones To Bona Fide Catalystsmentioning
confidence: 97%